Die Relevansie van God se Soewereiniteit en Verbond met betrekking tot die Onderwys - Aucamp, B. B.; van Niekerk, E. J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2005)
In this article the nature of reformational Christian education is explained from the perspective of the sovereignty of God and his covenant. The triune God is sovereign and therefore can lay claim to the whole of human life in relation to all aspects of reality; thus also education. Education also needs to be guided by the covenant between God and man. From this vantage point the view of man and child, values, subject teaching, standards and reformational reflection that should guide Christianreformational education is considered.